FRI0088 Synovial pathobiology correlates with diagnostic subgroups in early inflammatory arthritis: results from the pathobiology of early arthritis cohort (PEAC). (15th June 2017) - Lliso-Ribera, G; Humby, F; Kelly, S; Bombardieri, M; Lewis, M; Hands, R; Rocher, V; Bene, F; Nerviani, A; Buckely, C; Taylor, P; McInnes, I; et al.
Abstract : Background: Application of the 2010 ACR/EULAR Criteria for RA to early inflammatory arthritis cohorts permits an enhanced sensitivity for diagnosis compared to the historic 1987 ACR criteria but risks loss of diagnostic specificity. Heterogeneity in RA synovial pathobiology is well recognised with differences in qualitative and quantitative degree of immune cell infiltration, whether such heterogeneity correlates with classification criteria in early inflammatory arthritis is unknown, offering the potential to refine early diagnostic criteria. Objectives: The aim of this study was to examine in a cohort of therapy naïve, early inflammatory arthritis patients whether synovial immune cell infiltration differed significantly between diagnostic categories of early inflammatory arthritis (ACR/EULAR 2010 vs ACR 1987 vs undifferentiated). Methods: A total of 200 consecutive DMARD naïve early arthritis patients (disease duration <1 year) recruited as part of the multicentre PEAC study at Barts Health NHS Trust were categorised according to the following criteria: i. RA 1987 ACR, ii. RA 2010 ACR/EULAR, and iii. Undifferentiated Arthritis (UA). All patients underwent a baseline synovial biopsy of a clinically active joint along with collection of demographic data. Following H&E staining, degree of synovitis was assessed. Sections underwent immumohistochemical staining and semi-quantitative scoring (0–4) to determine the degree of CD20+Bcells, CD3+T cells, CD68+ lining (l) and sublining (sl) macrophage and CD138+ plasma cell infiltration. Sections were categorised into three pathotypes: (i) Fibroid: (CD68 SL<2 and or CD3, CD20, CD138<1), (ii) Myeloid: (CD68SL>2, CD20<1 and or CD3>1) and (iii) Lymphoid: (grade 2–3 CD20+ aggregates, CD20>2). Results: 166/200 samples were suitable for analysis. 115 patients were classified as RA1987, 16 patients as RA 2010 ACR/EULAR and 35 as UA. 80% of synovial samples were collected from small joints (wrist, MCP, PIP). Although there were no significant differences in disease duration between diagnostic subgroups, patients classified as RA1987 criteria had significantly higher levels of CRP, tender and swollen joints, DAS28 and sero positivity for ACPA and RF. When patients were stratified into pathotypes, a numerically higher proportion of patients within the RA1987 group were categorised as lymphoid. Further, patients within the RA 1987 group had a significantly higher synovitis score and degree of immune cell infiltration. Conclusions: Stratifying patients according to baseline clinical diagnosis translates into differences in synovial pathobiology. The capacity to refine early clinical classification criteria through application of synovial pathobiological markers offers the potential to predict disease outcome and stratify therapeutic intervention. Disclosure of Interest: None declared